Paciente masculino de 6 años de edad con Bronquitis Aguda. - Jiménez Vera, Carlos Isai (2020)
It has been shown that the effectiveness in the execution of interventions in respiratory problems has been very important and, above all, a staff that is highly trained and trained to perform this type of procedures will be of great help in order to improve the health status of the people suffering from respiratory pathologies, as in this case, acute bronchitis is one of the diseases that attacks the population to a great extent, with a high percentage in adults and in a lower percentage in children, without ruling out that they are also a vulnerable group. Acute bronchitis is a pathology that occurs when the bronchial tree becomes inflamed, it is generally caused by viruses or bacteria. Its symptoms are cough, sputum that may be whitish or greenish, slight dyspnea and noise when it comes to inhaling. For treatment it is recommended to hydrate or humidify the airways with the prescribed medication, bronchodilators are used to relax the bronchial muscles and thus allow the correct flow of oxygen.